2006
DOI: 10.1063/1.2354034
|View full text |Cite
|
Sign up to set email alerts
|

Control of p- and n-type conductivities in Li-doped ZnO thin films

Abstract: Li-doped ZnO films were prepared by pulsed laser deposition. The carrier type could be controlled by adjusting the growth conditions. In an ionized oxygen atmosphere, p-type ZnO was achieved, with the hole concentration of 6.04×1017cm−3 at an optimal Li content of 0.6at.%, whereas ZnO exhibited n-type conductivity in a conventional O2 growth atmosphere. At a Li content of more than 1.2at.% only high-resistivity ZnO was obtained. The amount of Li introduced into ZnO and the relative concentrations of such defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(60 citation statements)
references
References 19 publications
5
55
0
Order By: Relevance
“…Despite the formation of self-compensating donors, encouraging experimental results on Li-doped p-type ZnO were reported by Ye et al by using a dc reactive magnetron sputtering system [24][25][26][27]. The optimized p-type ZnO was achieved with a resistivity of 16.4 Ω cm, Hall mobility of 2.65 cm 2 /V s, and hole concentration of 1.44 × 10 17 cm −3 .…”
Section: Group I P-type Dopingmentioning
confidence: 77%
See 2 more Smart Citations
“…Despite the formation of self-compensating donors, encouraging experimental results on Li-doped p-type ZnO were reported by Ye et al by using a dc reactive magnetron sputtering system [24][25][26][27]. The optimized p-type ZnO was achieved with a resistivity of 16.4 Ω cm, Hall mobility of 2.65 cm 2 /V s, and hole concentration of 1.44 × 10 17 cm −3 .…”
Section: Group I P-type Dopingmentioning
confidence: 77%
“…Assuming the donor binding energy is about 50 meV, the Li acceptor level can be estimated to be near 300 meV. This level could be the second Li acceptor level as observed by Ye et al [24][25][26][27].…”
Section: Group I P-type Dopingmentioning
confidence: 88%
See 1 more Smart Citation
“…Comparable behavior has already been reported by Polarz et al and Lu et al who demonstrated that ZnO:Li with Li concentrations below 1 % reveals the best results regarding p-doping. [4,5] Thus, the Li related luminescence band indicates an efficient Li incorporation on Zn lattice sites up to a maximum Li concentration of about 0.56 %, which is accompanied by a pronounced formation of intrinsic point defects such as oxygen vacancies. It should be noted that the shallow Li-related donor-acceptor pair (DAP) emission at 3.05 eV reported by Meyer et al is not observed in these samples.…”
Section: Resultsmentioning
confidence: 98%
“…[3,4] Lu et al claimed doped films to be p-type for Li concentrations up to 1.2 %, with a maximal hole concentration at 0.8 % lithium. [5] However, there are only a few reports on Raman spectroscopy on such samples. Since Raman spectroscopy is a powerful tool for the investigation of different crystal properties, it can reveal important structural information such as strain and crystal quality or provide information about carrier concentrations due to phonon plasmon coupling (LPP).…”
Section: Introductionmentioning
confidence: 99%